UMPSA appointed as the Secretariat of MPEN Pahang - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KUANTAN, 6 December 2023 - The Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has been appointed as the Secretariat of the Pahang State Economic Advisory Council (MPEN).